Pre-Existing Inequality: The Impact of COVID-19 on Medicare Home Health Beneficiaries - Cabin, William (Home Health Care Manag Pract, 2021)
There is significant data on the adverse impact of COVID-19 on persons who were poor, minorities, had compromised physical or mental health, or other vulnerabilities prior to the COVID-19 pandemic. A significant portion of the overall Medicare population has such vulnerabilities. The Medicare home health beneficiary population is even more vulnerable than the overall Medicare population based on gender, race, income level, living alone status, and number of chronic conditions. A literature review indicates there is only 1 study on the impact of COVID-19 in Medicare home health on home care workers and none on the impact on home health beneficiaries. The current study is a qualitative study based on interviews of a convenience sample of 48 home care nurses from 9 different home health agencies in New York City between April 1 and August 31, 2020. Six major themes emerged: need for social service supports increased; loneliness and depression increased among patients; physical and mental health conditions became exacerbated; substance use and abuse increased; evidence of domestic violence against patients increased; and there was a limited amount of staff and equipment to care for patients.